Hepatitis C and the limits of medicalisation and biological citizenship for people who inject drugs - Fraser, Suzanne (Routledge, 2010)
People who inject drugs access information about hepatitis C in a range of ways. For some, diagnosis is a key point at which information is encountered. This information is considered in public health circles to be important for initiating or enhancing safe injecting practice and self-care. Yet, not all of those diagnosed with hepatitis C continue to stay informed about the disease or about their health in general, preferring to postpone engagement with these issues. In this article, I draw on Nikolas Rose's idea of biological citizenship and interview material gathered from people who inject drugs, who have been diagnosed with hepatitis C to conduct an analysis of this deferral. Drawing on the empirical material, I note that in some cases, pursuing knowledge is sometimes overshadowed by more pressing material concerns such as homelessness. In other cases, the desire to acknowledge or confront the implications of the infection is absent to the point that 'keeping up' is not regarded as desirable. In other cases still, the information imparted at diagnosis is so incomplete that the merits of seeking further medical input are seen to be doubtful. Drawing on the theoretical material, the article asks, what kind of medical subjects, or biological citizens, are these interview participants, given their parallel status as hepatitis C patients and subjects of discourses of addiction I conclude by considering the effectiveness of the medicalisation of addiction.